Development of Science and Student Mindsets Toward Muhammadiyah Al-Islamiah through Information Technology and Artificial Intelligence - Prasetyo, Tri Ferga; Sismadi, Wawan; Fathurohman SW, Oman (Al-Mau’izhoh: Jurnal Pendidikan Agama Islam, 2025)
Artificial Intelligence (AI) in strengthening student mindsets regarding the values of Al-Islam and Kemuhammadiyahan (AIK) within Muhammadiyah Higher Education institutions. Amidst the disruption of the Industrial Revolution 4.0, this paper analyzes how technology can serve as a catalyst for the Tajdid (reform) movement. Using a qualitative descriptive method supported by simulated perception data, the research objectives are focused on evaluating digital readiness and ethical considerations in religious education. The results indicate that students possess a high level of technological readiness, with a specific emphasis on the urgency of an "Islamic AI Ethics" framework, scoring 4.7/5. The key finding is theoretical in nature, concluding that utilizing AI as a personalized cognitive assistant can accelerate the internalization of Muhammadiyah’s progressive Islamic ideology. However, implications show that the development of an authoritative, institution-verified data repository is crucial to ensuring digital dakwah remains grounded in authentic Muhammadiyah methodology, specifically Manhaj Tarjih.